Guerres et jeux vidéo : représentations et enjeux de mémoire de la Seconde Guerre mondiale - Thomas Facchini (Amnis)
Many videogames uses history and particularly the World War II in their scenario. This article is divided into two main parts. The first is the evolution of videogame representations of the Second World War in the 2000s and various aesthetic (temporal, visual and sound) of combat that are reflected in these games. The second Part relates the questions of the controversy in Russia about the videogame Company of Heroes 2, released in 2013 in which the action takes place on the Eastern Front. Russian accuses the game to show a bad image of the Red Army and focus on Soviet crimes. This polemic is analyzed in light of the political context and memory of Russia. The World War II, called the « Great Patriotic War », is exploited for a national identity construction.